Styl czy dyskurs naukowy? Perspektywa historyczna - Rejter, Artur (Forum Lingwistyczne, 2018)
Academic Style or Discourse? A Historical Perspective The work concerns the usefulness of terms “style” and “discourse” in research of academic Polish evolution. One notices the significant advantages of complementary interpretation of research on the academic Polish evolution. The analysis of style level ensures description of basic and essential – both: stable and changeable – language features, systemic, but stylistically worked. On the other hand the reference to discourse level enables to describe and interpret the phenomena of academic communication in broader aspects, taking into consideration the socio-cultural contexts, which determine the forming of academic Polish in prototype shape, but also its contemporary dissolving in postmodern communication reality. Furthermore, the discourse context opens the research for extralinguistic conditions, previously neglected in analysis of language dynamics. Key words: academic style, academic discourse, text, history of Polish, stylistics